(untitled) (Journal of Libya for geographical studies, 2024)
The map is one of the most important factors of visual analysis, and the tool that geography needs in the study, whether for natural phenomena or human phenomena, especially after Geographic Information Systems (GIS) technology, so this study dealt with population distribution maps, which is one of the most important distribution maps for geographical phenomena, and new population change maps were prepared and designed using Arc gis10.5, based on population data for the years 2006-2016, the study relied on traditional cartographic methods in the preparation of maps, as well as raster for representing Population Registration and methods for representing interval quantities (The corobleth method) to represent population densities, in addition to using the multiple representation method (the corobleth method and the proportional circles method) to represent the density, and then implement all maps on Arc Gis 10.5, the study found that the gradient method is one of the most successful methods available in the GIS program to produce population density maps, and has been applied to the corner area.